2018
DOI: 10.11113/mjfas.v14n4.1218
|View full text |Cite
|
Sign up to set email alerts
|

Low cost palm oil fuel ash based ceramic membranes for oily water separation

Abstract: Ceramic membranes have been gaining so much interest for oily water separation due to their superior characteristics such as good anti-fouling property, superhydrophilic, as well as excellent thermal and chemical stabilities. However, ceramic membranes are very expensive which hinders their uses in large scale applications. Therefore, the aim of our study is to develop a low cost palm oil fuel ash (POFA) based ceramic hollow fiber ceramic membrane for oily water separation application. An asymmetric membrane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Research on HFM and its versatile applications increased continually and rocketed in the past two decades (2001–2020) with a total of 5626 research articles, achieving the highest figure in the year 2018 (375 articles), as shown in Figure 1 . This variation trend of research papers reflected the development process of HFM applications specifically for gas separation and water treatment technology [ 3 , 37 ]. Factors such as increasing problems of water pollution and water scarcity with an increasing global population contributed to the development of new methods for water purification.…”
Section: Resultsmentioning
confidence: 99%
“…Research on HFM and its versatile applications increased continually and rocketed in the past two decades (2001–2020) with a total of 5626 research articles, achieving the highest figure in the year 2018 (375 articles), as shown in Figure 1 . This variation trend of research papers reflected the development process of HFM applications specifically for gas separation and water treatment technology [ 3 , 37 ]. Factors such as increasing problems of water pollution and water scarcity with an increasing global population contributed to the development of new methods for water purification.…”
Section: Resultsmentioning
confidence: 99%
“…37.5 wt.% heattreated RH content and 1200ºC sintered specimen shows bending strength of ~71 MPa, open porosity of ~50% and permeate water flux of ~300 L/m 2 •h. Tai et al (2018) [242] have synthesized hollow fiber ceramic membrane for oily water separation using waste palm oil fuel ash (it is generated through the burning of palm kernel shells, empty fruit bunches and mesocarp fiber) through the combination of phase inversion and sintering method. 38 wt.% palm oil fuel ash containing 1050°C sintered membrane shows 96% oil rejection efficiency and 185.42 L/m 2 •h permeate flux at 3 bar applied pressure.…”
Section: Ceramic Membranesmentioning
confidence: 99%
“…Sekitar 4,5 juta ton limbah padat kelapa sawit, khususnya abu terbang cangkang sawit diproduksi per tahun, data ini menunjukkan potensi abu terbang cangkang sawit sebagai bahan baku adsorben untuk menghilangkan kandungan Arsen pada air limbah (Yusof et al, 2020). Penggunaan abu terbang cangkang sawit cukup layak dan juga menarik untuk dilakukan karena abu terbang cangkang sawit yang tidak diolah (raw) mengandung 68% SiO 2 (Tai et al, 2018). Selain itu, abu terbang cangkang sawit merupakan adsorben yang murah (Yanyan et al, 2018), terbarukan, dan menunjukkan pelepasan karbon dioksida yang rendah (Elias et al, 2018).…”
Section: Pendahuluanunclassified